The bioactive properties of selenium enriched Allium sativum (garlic) - Kirk, Charlotte (2024)
Selenium (Se) is an essential micronutrient for human health, low Se status has been found to predispose people to multiple health conditions. Se is obtained through dietary sources, however intake of Se is decreasing within the UK population, due to multiple factors including low Se soils and shifts in dietary patterns. Crops are generally low in Se, biofortification methods aim to increase the Se content. However, there is a narrow therapeutic window of Se supplementation and the toxicity of Se is poorly understood therefore there is concern that enriching food crops with Se without further understanding of toxicity could have adverse effects. The aim of this work was to enrich garlic, a widely consumed food crop with Se, and assess the bioactivity of the plant tissues and further the understanding of Se toxicity mechanisms.